Advances in hepatitis c - Mauro, Ezequiel; Marciano, Sebastián; Galdame, Omar; Gadano, Adrián (Revista del Hospital Italiano de Buenos Aires, 2014)
Hepatitis C is the leading cause of chronic hepatitis, cirrhosis, and liver cancer in Argentina, where from 1.5% to 2.5% of adults are infected. It is estimated that more than half of the infected people are not aware of their infection. It is of great importance to identify all infected people in order to treat them and prevent disease progression, hepatic decompensation, and hepatocellular carcinoma. Great advances were achieved the last years in the treatment of Hepatitis C. By the time this manuscript was submitted, approximately 70% of the patients with chronic Hepatitis C could be cured with the available drugs in Argentina. In the near future, 90% of the infected patients will be cured with new antivirals that are about to be approved. However, difficultto-treat patients, such as those with decompensated cirrhosis, patients in hemodialysis, and those with other significant co-morbidities, might not be candidates to treatment and their management will remain challenging